Transparent Al-Doped ZnO Thin Films for High-Sensitivity NO2 Gas Sensing - So-Young Bak; Se-Hyeong Lee; Hyeongrok Jang; Minseong Kim; Sungjae Kim; Moonsuk Yi (Sensors, 2025)
This study developed a transparent NO2 gas sensor with enhanced sensing performance and high optical transmittance. Al-doped ZnO thin films were deposited by atomic layer deposition, which was chosen for its capability to precisely control surface chemistry at the atomic scale. Oxygen vacancies were effectively introduced by utilizing trimethylaluminum, a strongly reducing Al2O3 precursor, thereby increasing carrier concentration and enhancing gas-sensing performance. By adjusting the Al doping level, the optimized device achieved a 50 °C reduction in operating temperature, a 66.2-fold increase in sensitivity at 150 °C, and shortened response and recovery times. The morphology, crystallinity, and elemental distribution were analyzed using transmission electron microscopy, selected area electron diffraction, and energy-dispersive X-ray spectroscopy, while chemical bonding states were investigated via X-ray photoelectron spectroscopy. Optical properties were characterized using UV–visible spectroscopy, confirming an average transmittance of approximately 80% in the visible range. These results demonstrate the promise of transparent oxide gas sensors for integration into next-generation electronics and Internet of Things-based environmental monitoring systems.